Diffuse large B-cell lymphoma: Time to focus on circulating blood nucleic acids?. (May 2021) - Regazzo, Giulia; Marchesi, Francesco; Spagnuolo, Manuela; Díaz Méndez, Ana Belén; Masi, Serena; Mengarelli, Andrea; Rizzo, Maria Giulia
Abstract: Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous neoplasm with diverse genetic abnormalities and outcomes. To date, DLBCL is invasively diagnosed by tissue biopsy and few biomarkers are available to predict patient outcome, treatment response and progression. The identification of patient-specific biomarkers would allow a "personalized medicine" approach for DLBCL patients. In this regard, "liquid biopsies" hold great promise, capturing the entire genetic landscape of the tumour and allowing a rapid and dynamic management of cancer. Liquid biopsy studies particularly focus on cell-free nucleic acids, such as cell-free DNA (cfDNA) and microRNAs, which are easy to collect and analyse. In accordance with the PRISMA criteria, we performed a systematic review on circulating nucleic acids as potential biomarkers for DLBCL management. The results suggest that combining information from the genetic (cfDNA) and epigenetic (microRNAs) landscape of the disease could lead to developing an integrated network of non-invasive biomarkers for the better management of DLBCL.